Ultrasound‐guided intermediate cervical plexus block for carotid endarterectomy using a new anterior approach: a two‐centre prospective observational study1. (1st December 2014) - Calderon, A. L.; Zetlaoui, P.; Benatir, F.; Davidson, J.; Desebbe, O.; Rahali, N.; Truc, C.; Feugier, P.; Lermusiaux, P.; Allaouchiche, B.; Boselli, E.
Summary The aim of this prospective, double‐centre, observational study performed in 116 patients was to describe a new anterior approach of ultrasound‐guided intermediate cervical plexus block for carotid endarterectomy. The median (IQR [range]) volume of ropivacaine 0.5% administered was 30 (25–30 [20–45]) ml. Supplemental local anaesthesia (infiltration and topical) was needed in 66 (57%) patients. Overall, 41 (35%) patients needed additional sedation (18 midazolam; 23 remifentanil). There was no intra‐operative complication or systemic toxicity of ropivacaine. One regional anaesthesia procedure was converted to general anaesthesia because of patient agitation. Adverse effects were of short duration and did not affect surgery. Satisfaction scores were high for 92 (79%) patients (63 satisfied; 29 very satisfied) and 104 (90%) surgeons (51 satisfied; 53 very satisfied). This study shows that the ultrasound‐guided intermediate cervical plexus block using an anterior approach is feasible and provides similar results to other regional techniques during carotid endarterectomy.